Active droplet/bubble generation and measurement in microfluidics - Chong, Zhuang Zhi (2016)
This thesis deals with in-situ measurement and active control of droplet/bubble generation using ultrasonic. The capability of injection molded PMMA device as a droplet generator was evaluated by characterizing the generated droplets under different sets of flow rates. A fully-automated video processing software application: Automatic Droplet Measurement (ADM) capable of in situ measurement has been built. This new software is faster than any existing available software and thus serves as an invaluable and efficient tool for droplet/bubble generation research. The ADM software has been publicly released for free. Active control opens up a new space of degree of freedom to actuate and manipulate droplet/bubble sizes. A new method to control bubble generation using an ultrasonic transducer system has been developed. The gas–liquid oscillated by the system induces acoustic streaming, which increases the gas flow rate and bubble size significantly. The change in bubble size is repeatable with response in seconds. The same system has also been used to vibrate the oil-water interface for active droplet generation control. However, the effect is not as significant.